Surgical approach to lobectomy for non-small cell lung cancer: a narrative review of open, thoracoscopic, and robotic techniques - Nguyen, Kenny; Valderrama, Adrian; Vasic, Ivana; Velotta, Jeffrey B. (Video-Assisted Thoracic Surgery; Vol 11 (June 30, 2026): Video-Assisted Thoracic Surgery, 2026)
Background and Objective: Lung cancer remains the leading cause of cancer-related mortality worldwide, with non-small cell lung cancer (NSCLC) comprising the majority of cases. For early-stage NSCLC, surgical resection remains the gold standard, with lobectomy representing the predominant surgical approach. Over the past three decades, operative approaches have evolved from open thoracotomy to minimally invasive video-assisted thoracoscopic surgery (VATS), and most recently, robotic-assisted thoracoscopic surgery (RATS). Despite increasing adoption of minimally invasive approaches, no randomized controlled trial has directly compared all three modalities. This review aims to compare outcomes across open, VATS, and RATS lobectomy, focusing on perioperative and oncologic outcomes, quality of life, and cost-effectiveness.Methods: A literature search was conducted in PubMed for studies published from January 1, 2015 through September 1, 2025. Search terms included “non-small cell lung cancer”, “lobectomy”, “open”, “VATS”, “RATS”, “outcomes”, and “cost”. Eligible studies included randomized controlled trials, cohort studies, meta-analyses, and reviews published in English that reported lobectomy outcomes in adult NSCLC.Key Content and Findings: VATS and RATS achieve oncologic outcomes equivalent to open lobectomy, with improved short-term outcomes such as reduced blood loss, shorter length of stay, and lower complication rates. VATS is well established, though some studies suggest lower lymph node harvest compared with open surgery. RATS offers enhanced visualization and dexterity, with reduced conversion rates compared to VATS, though at the expense of longer operative times and higher costs. Quality-of-life studies favor minimally invasive approaches over thoracotomy, with some domain-specific advantages observed for robotic surgery. Cost analyses suggest RATS may be economically favorable compared to thoracotomy but remains less cost-effective than VATS in most contexts.Conclusions: Both VATS and RATS represent safe and effective alternatives to thoracotomy for lobectomy in NSCLC. While VATS remains more cost-efficient, RATS may offer technical and oncologic advantages in select patients. Future research should prioritize randomized comparisons, long-term outcomes, and health system-specific cost analyses to optimize surgical decision-making in thoracic oncology.